2021
DOI: 10.1186/s40793-021-00376-z
|View full text |Cite
|
Sign up to set email alerts
|

Coupled microbiome analyses highlights relative functional roles of bacteria in a bivalve hatchery

Abstract: Background Microbial communities are ubiquitous throughout ecosystems and are commensal with hosts across taxonomic boundaries. Environmental and species-specific microbiomes are instrumental in maintaining ecosystem and host health, respectively. The introduction of pathogenic microbes that shift microbiome community structure can lead to illness and death. Understanding the dynamics of microbiomes across a diversity of environments and hosts will help us to better understand which taxa foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Here, we strengthened these results using a metaproteomic approach that provided an independent functional measure of the microbiome-host crosstalk. Similarly to other multi-omics studies (54,55), we found discrepancies between the quantitative proteome pro les and the DNA-based relative abundance of individual species. These differences likely stem from complex regulatory networks along the gene to protein expression path, which differ between microbial kingdoms.…”
Section: Discussionsupporting
confidence: 67%
“…Here, we strengthened these results using a metaproteomic approach that provided an independent functional measure of the microbiome-host crosstalk. Similarly to other multi-omics studies (54,55), we found discrepancies between the quantitative proteome pro les and the DNA-based relative abundance of individual species. These differences likely stem from complex regulatory networks along the gene to protein expression path, which differ between microbial kingdoms.…”
Section: Discussionsupporting
confidence: 67%
“…Complementary approaches (including various 'omics, microscopy techniques, (epi)genetics, and immunology) integrating microbiome studies with host and environmental factors will allow us to better understand the dynamics of microbiota across a diversity of environments and hosts and should help us to identify, for example through network interaction studies, taxa predictive of survival as well as mortality events [54,55]. The more comprehensive understanding that is resulting from these integrated approaches will enable us to better manage bivalve aquaculture, and mitigate problems.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome of bivalves is thought to play an essential role in host health and disease. The bacterial component of the bivalve microbiome is known to be involved in a range of functions, including digestion, nutrient cycling, and immune defense (Pierce and Ward, 2018;Timmins-Schiffman et al, 2021). Studies have shown that some bacteria in the bivalve microbiome produce antimicrobial compounds that help protect the host from pathogens (Destoumieux-Garzoń et al, 2020;Balbi et al, 2021).…”
Section: Bivalve Microbiomementioning
confidence: 99%